MRI of normal brain maturation. - Holland, B A; Haas, D K; Norman, D; Brant-Zawadzki, M; Newton, T H (American Journal of Neuroradiology, 1986)
The unprecedented gray/white differentiation obtained with magnetic resonance imaging (MRI) has created a unique opportunity to trace the normal process of myelination. Fifty-nine children referred for evaluation of a nonneurologic problem or a nonspecific neurologic complaint were studied with MRI using spin-echo technique. Children ranged in age from term (40 weeks intrauterine) to 16 years. Scans were reviewed for quantitative and qualitative changes with age. T1 and T2 relaxation times were measured for 13 regions of interest in 37 children. With increasing age a sharp decrease in both T1 and T2 values, most pronounced during the first year of life, was seen. The prolonged relaxation times in the newborn infant correspond to the known high water content of the neonatal brain; the subsequent decline corresponds to the decrease in water content and increase in myelination observed in autopsy studies of infants. Qualitative changes in the MRI appearance of the brain with age using a spin-echo sequence (2 sec repetition time) demonstrated that the process of myelination was most rapid during the first 2-3 years of life. Myelination appeared to occur earliest in the posterior fossa, with the middle cerebellar peduncle identifiable at only 3 months. By the age of 1 year, all major white matter tracts including the corpus callosum, subcortical white matter, and the internal capsule were well defined. However, due to subtle changes in appearance, the refined configuration of the adult brain was not attained until early adolescence.